Electronic effects of aromatic rings on the catalytic activity of ‎dioxidomolybdenum(VI)-hydrazone complexes - Bikas, Rahman; Lippolis, Vito; Noshiranzadeh, Nader; Farzaneh-Bonab, Hossein; Blake, Alexander J.; Siczek, Milosz; Hosseini-Monfared, Hassan; Lis, Tadeusz (Wiley, 2016)
Nine dioxidomolybdenum(VI) complexes were synthesized by the ‎reaction of MoO3 with tridentate hydrazone Schiff base ligands ‎obtained from the reaction of aromatic acid hydrazides (3-hydroxy-2-‎naphthoic acid hydrazide, 4-pyridine carboxylic acid hydrazide or 2-‎furane carboxylic acid hydrazide) and ortho-hydroxy aldehyde ‎derivatives (5-iodo-2-hydroxybenzaldehyde, 2-hydroxy-1-‎naphthaldehyde or 2-hydroxy-3-methoxybenzaldehyde). All ligands ‎and complexes were characterized by elemental analysis and ‎spectroscopic methods. The structures of seven complexes were ‎further elucidated by single-crystal X-ray diffraction analysis which ‎indicated a distorted octahedral geometry at the metal centre. ‎Spectroscopic and X-ray analyses indicated that the ligands are ‎coordinated to the molybdenum(VI) ion as dinegative ligands due to ‎deprotonation of phenolic OH and amidic NH groups upon ‎complexation. These complexes were used as catalyst in ‎the oxidation of cyclooctene and thioanisol in the presence of ‎hydrogen peroxide as environmental friendly oxidant. In order to ‎achieve the highest catalytic activity, the effects of important ‎parameters such as solvent, temperature and the molar ratio of ‎oxidant to substrate were optimized. The results indicate that ‎electron-withdrawing substituents on the ligands increase the ‎catalytic activity of dioxidomolybdenum(VI)-hydrazone complexes.‎